Enhancing the Enabling Environment to Promote Private Sector Participation in the Implementation of the Philippine Water Supply and Sanitation Master Plan - Castro, Aileen (World Bank, Washington, DC, 2018)
The main objective of the discussion note is to inform dialogues among Government policy makers and other stakeholders on how to move forward with the critical water supply and sanitation (WSS) sector reforms in the Philippines, focusing on how private sector participation might be harnessed to help achieve the universal access to safe and sustainable water supply and sanitation services. The note aims to provide an initial analysis on: (i) current trends of private participation in the water sector, (ii) the liquidity of the commercial finance markets to support these activities, (iii) any current challenges or bottlenecks in financing the private sector (including issues relating to the enabling environment), and (iv) possible solutions to encourage effective investment into the sector. During the roundtable discussion, both the public and private sector providers confirmed that they would be willing to enter into less commercially viable service areas, provided there was substantial support from the government in the form of capital grants that would make the projects viable, and might even be able to leverage commercial finance. Hence, the discussion note proposed to: a) set up Project Preparation Facility, b) strengthen the government joint venture guidelines and PPP Act, and c) promote Blended Finance.